2021
DOI: 10.1038/s41598-021-85841-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive olfactory learning in Drosophila

Abstract: Olfactory learning and conditioning in the fruit fly is typically modelled by correlation-based associative synaptic plasticity. It was shown that the conditioning of an odor-evoked response by a shock depends on the connections from Kenyon cells (KC) to mushroom body output neurons (MBONs). Although on the behavioral level conditioning is recognized to be predictive, it remains unclear how MBONs form predictions of aversive or appetitive values (valences) of odors on the circuit level. We present behavioral e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 71 publications
3
24
1
Order By: Relevance
“…But an individual fly will make its own decision” (cited by [ 39 ]). Similar observations as in the quote were described for flies conditioned to prefer a particular odor [ 40 ] and recently mentioned again in [ 41 ]. In both cases, the setup used was similar to the classic countercurrent phototaxis paradigm (CPP) developed by Benzer, where flies have several opportunities in one session to approach a light source and the population ends up being split according to how many times each fly chose approaching the light [ 42 ].…”
Section: Introductionsupporting
confidence: 86%
“…But an individual fly will make its own decision” (cited by [ 39 ]). Similar observations as in the quote were described for flies conditioned to prefer a particular odor [ 40 ] and recently mentioned again in [ 41 ]. In both cases, the setup used was similar to the classic countercurrent phototaxis paradigm (CPP) developed by Benzer, where flies have several opportunities in one session to approach a light source and the population ends up being split according to how many times each fly chose approaching the light [ 42 ].…”
Section: Introductionsupporting
confidence: 86%
“…In vertebrates, it has been shown that prediction error coding dopaminergic neurons (DANs) are involved in learning ( Schultz et al, 1997 ; Schultz, 2016 ). Recent studies give rise to the assumption that DANs could play a similar role in Drosophila melanogaster ( Hammer, 1997 ; Riemensperger et al, 2005 ; Ichinose et al, 2015 ; Eichler et al, 2017 ; Felsenberg et al, 2017 , 2018 ; Zhao et al, 2021 ; Eschbach et al, 2020 ) and other insects ( Terao and Mizunami, 2017 ), rejuvenating an earlier hypothesis based on experimental observations in the honeybee ( Hammer, 1997 ).…”
Section: Introductionmentioning
confidence: 90%
“…In the mushroom body, dopaminergic neurons potentially compute novelty by combining excitatory inputs from olfactory sensory channels with inhibitory inputs driven by familiarity encoding interneurons (Zhao et al, 2021) (and see Discussion). If TH-positive cells were to play a similar role in the SEZ, then they would be predicted to receive direct or indirect inputs from taste sensory neurons as well as input from familiarity-representing inhibitory neurons.…”
Section: Sensory Neurons Projections In Sez Overlap Spatially With Projections Of Th-neuronsmentioning
confidence: 99%